OCCULT PHENOMENA IN SHERLOCK HOLMES THE MOVIE - NAMAZCARRA, CHRIESHER (Jurnal Ilmiah Mahasiswa FIB, 2014)
Keywords: Occult phenomena, Sherlock Holmes, movie. Lately, it is not difficult for people to find occult practices. There are many television programs and movie which air mystical programme aggressively to raise the rating and attract the viewers. A movie that raise occultism theme is Sherlock Holmes, the Movie. This movie tells about the struggle of detective Sherlock Holmes to fight the black magic power of Lord Blackwood.To carry out the study, the theories of Occultism such as the secrecy, meditation, hypnosis, and ideals of occultism will be applied. Occultism is generally attributed to the knowledge and practices associated with the supernatural phenomena to obtain a secret power. This theory will be used to analyze the events that contain the occult symbol including the secrecy of black magic ritual and the occult killings that have been done by Lord Blackwood in Sherlock Holmes, the Movie.The result of the study shows that Blackwood misuses science to bring fear to society. Detective Holmes solves the mistery behind Blackwood’s black magic power. Holmes also tries to learn and practice the occult science in order to find out the technique of the occult trick.The next researchers can conduct a deeper research by exploring more about the iluminati aspect found in the movie and how the society respons to the freemasonry ideology.